The Responsibility of Forms: Critical Essays on Music, Art, and Representation - Barthes, Roland 1915-1980; Howard, Richard (Berkeley, CA University of California Press, 1985)
These late essays of Roland Barthes's are concerned with the visible and the audible, and here the preoccupations are particularly intense and rewarding, in part because Barthes was himself, by predilection, an artist and a musician, and in part because he was of two minds about the very possibility of attaching to art and to music a written text, a criticism.
Keywords: 20th Century (1901-2000); Esthetics; France